The role of islamic spirituality in the management and leadership process - Mahazan Abdul Mutalib; Rafiki, Ahmad 1981- (2021)
Leaders nowadays need to know, learn, and apply the concept of qalb leadership where it has been taught by the Prophet Muhammad as well as explained by Islamic scholars. The comparison with other mindful leadership concepts is required to provide solutions and options in leadership for better outcomes and spiritual awareness. It is found that leadership literature, in general, is unable to generate an understanding of a leadership concept that is both intellectually compelling and emotionally satisfying. As for qalb leadership, it focuses on the spirituality of leadership that can aid in facing unpredictable manners and provide better outcomes for followers. Research on Islamic leadership and spirituality may pave the way for better leadership practices in the future.The Role of Islamic Spirituality in the Management and Leadership Process will elaborate the spirituality and qalb in human life and leadership along with providing a discussion on the role and function of qalb in the overall leadership process. Through spirituality, human interdependence, creativity, and social justice can be created and molded. This type of leadership enables transformation in a natural way without denying basic human nature and imparts balance to both the outer and inner needs of humans. With the discussion of four cardinal virtues of Al-Ghazali, leaders can solve many problems that emerge in their organizations. This book is ideal for managers, executives, theologians, professionals, researchers, academicians, and students who are interested in how Islamic spirituality plays a role in leadership
Keywords: Aufsatzsammlung